Analisis Kepemimpinan Musa: Teladan Dan Relevansi Bagi Pemimpin Modern - Novi Krisdyanti; Sunday Lantun Paringanan; Selim Randana’; Yainal Lion Matasak (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This paper aims to investigate and analyze Moses' leadership character in a historical context and consider his relevance as a role model for modern leaders. By detailing various aspects of Moses' leadership, such as courage, perseverance, and vision, this paper provides an in-depth look at how Moses' leadership principles can be applied and adapted in the contemporary leadership environment. This research involves collecting data from historical sources and related literature to present a comprehensive analysis.